2006
DOI: 10.1292/jvms.68.853
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Canine Glaucoma with Goniodysplasia in Japan: A Retrospective Study

Abstract: ABSTRACT. The incidence of primary and secondary glaucoma in dogs was investigated. A total of 1244 dogs received ophthalmologic examinations, including tonometry and gonioscopy. Goniophotographs were taken using a goniolens to evaluate the iridocorneal angle (ICA) as well as pectinate ligament (PL). The anterior width of the ciliary cleft and the total distance from the origin of the PL to the anterior corneal surface were measured from the goniophotographs. Glaucoma was diagnosed based on the cupping of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
0
21
0
1
Order By: Relevance
“…Kato, et al, reported that the Beagle breed has the fourth-highest incidence of canine glaucoma, after Shiba-Inu, Shih-Tzu, and American Cocker Spaniel breeds [18]. Kuchtey et al recently reported that the Gly661Arg variant (56097365 G>A) of ADAMTS10 in Beagles with POAG is a candidate, predictive gene allele for canine POAG [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kato, et al, reported that the Beagle breed has the fourth-highest incidence of canine glaucoma, after Shiba-Inu, Shih-Tzu, and American Cocker Spaniel breeds [18]. Kuchtey et al recently reported that the Gly661Arg variant (56097365 G>A) of ADAMTS10 in Beagles with POAG is a candidate, predictive gene allele for canine POAG [12].…”
Section: Discussionmentioning
confidence: 99%
“…Recent study reported the Gly661Arg variant in ADAMTS10 as the candidate disease-causing variant for POAG Beagles [12]. Kato et al investigated the incidence of canine POAG, and reported that Shiba-Inus exhibited the highest incidence of glaucoma among 29 breeds, followed by Shih-Tzus [18]. They also reported that an abnormal iridocorneal angle and dysplastic prectinate ligament were associated with a high incidence of glaucoma in Shiba-Inus and Shih-Tzus.…”
Section: Introductionmentioning
confidence: 99%
“…Goniodysgenesis: Background and Nomenclature GD, 3,4 also known as pectinate ligament dysplasia (PLD), 3,[5][6][7][8][9][10][11][12] or goniodysplasia 13,14 is a congenital ICA abnormality that, when extensive, may predispose to the development of glaucoma later in life. 3,10,15 A normal canine ICA (Figs.…”
Section: Glaucoma-induced Changes In the Canine Anterior Segmentmentioning
confidence: 99%
“…However, openangle glaucoma (OAG) is also a hereditary problem with the presence of glaucoma in one's family increasing the risk of developing glaucoma four-to nine-fold over that of individuals with no hereditary glaucoma background. 6 Among young adults, especially African-Americans, glaucoma is the leading cause of blindness, 7 which is 6-8 times more common than in Caucasians. 2 The American Hispanic population has the greatest risk of developing glaucoma more rapidly and at a younger age, 8 while people of Asian descent appear to have no significant risks of developing glaucoma.…”
Section: Loss Of Vision: Causes and Incidencesmentioning
confidence: 99%